Between Oñati and the world: Institution building for science – A personal testimony - Guibentif, P. (Oñati Socio-Legal Series, 2022)
The International Institute for the Sociology of Law was inaugurated precisely at the time I was so lucky to find myself in the position to start what I now feel I may legitimately call a socio-legal career. A career which has largely unfolded at a place not that distant from Oñati: Lisbon. Under these circumstances, answering the kind invitation of Martin Ramstedt to give an account of my working experience at the IISL, it makes sense to (1) summarize my own way to the sociology of law, (2) describe the development of the IISL as I was privileged to witness it since its inauguration, (3) survey the tasks I had to carry on during my directorship (1998-2000), and (4) recount the main opportunities I since then had to contribute to the Institute’s activities. Throughout this long period of involvement in the Oñati Institute’s life, I could appreciate its development as an institution, in the strong sense of the term. I will, therefore, (5) take the opportunity to tentatively revisit here the concept of institution, and to appreciate its relevance for reflecting our practice as scientists.